Roles of attention in perceptual learning from perspectives of psychophysics and animal learning - Tsushima, Yoshiaki (2009)
The role of attention in perceptual learning has been a topic of controversy. Sensory psychophysicists/physiologists and animal learning psychologists have conducted numerous studies to examine this role; but because these two types of researchers use two very different lines of approach, their findings have never been effectively integrated. In the present article, we review studies from both lines and use exposure-based learning experiments to discuss the role of attention in perceptual learning. In addition, we propose a model in which exposure-based learning occurs only when a task-irrelevant feature is weak. We hope that this article will provide new insight into the role of attention in perceptual learning to the benefit of both sensory psychophysicists/physiologists and animal learning psychologists.